Oxygen Transfer Characteristics for Airlift Bioreactor - Li, Hua; Chen, Wanren; Chen, Xiaoshuang (Asian Journal of Chemistry, 2010)
The fermentation experiment on biological fertilizer in 50 L airlift bioreactor has been studied. Oxygen mass transfer characteristic of cold and thermal model experiment and microbial growth condition in this reactor are also determined. It is found, that the biofertilizer fermentation using air lift bioreactor with static mixer can decrease fermentation period and increase facility efficiency compared with the traditional bioreactor. The mass transfer coefficient increases with the increase of gas flow rate, but decreases with the increase of liquid viscosity.